Factors associated with knowledge and adherence in tuberculosis treatment among healthcare workers with latent tuberculosis infection at HSAAS UPM - Daut, Ummi Nadira; Abdul Aziz, Tasnim (Asian Pacific Society of Respirology, 2024)
Despite the significance of latent tuberculosis infection (LTBI) treatment, its acceptance among healthcare workers (HCW) is lower than non-HCW. It is important to identify the factors that contribute to the lack of adherence to LTBI treatment among HCW.